Síntese, caracterização e avaliação da atividade fotoeletrocatalítica de filmes finos de Sb2S3 - Araújo, Moisés Albuquerque de (2020)
Photoelectrochemical cells (PECs) have been shown to be a promising system for H2 generation from photoelectrolysis of water. Among the semiconductors materials that have been studied for PECs, Sb2S3 stands out due to its superlative photoelectrocatalytic properties, and for having abundant and low toxicity elements. In the light of this, herein we proposed the synthesis and characterisation of the bare and modified Sb2S3 thin films for the hydrogen evolution reaction (HER) via photoelectrolysis of water. The modifications of this material consisted of obtaining the SnS/Sb2S3 heterostructure, treating the Sb2S3 films under nitrogen plasma, and depositing molybdenum sulphide (MoSx) upon the Sb2S3 films. Initially we studied the SnS/Sb2S3, the synthesis of this system involved obtaining the SbSn films by electrodeposition at different potentials on glass-coated FTO substrate. Subsequently, the films were sulphurised under sublimated sulphur atmosphere and characterised in terms of their physical, chemical, and optical properties. Regarding the photoelectrochemical assessment, we achieved a photocurrent density (jphoto) of −0.12 ± 0.01 mA cm−2 at −0.32 V for the sulphurised SnS/Sb2S3 films which were obtained at −1.14 V. This jphoto value was 40 and 12 times higher than the pure SnS and Sb2S3 films, respectively. Additional studies based on band diagrams of the SnS and Sb2S3 films indicated the formation of the type II heterostructure, which favoured transportation of the photogenerated electron and holes. Aiming to obtain higher values of jphoto, we evaluated the effect of treating the Sb2S3 films under nitrogen plasma at different span times. The Sb2S3 films treated under nitrogen plasma for only 10 s had a jphoto of −0.48 ± 0.04 mA cm−2 at −0.32 V; this corresponded to a 24-fold increase compared to the untreated film. This photoresponse enhancement may be linked to the increased degree of wettability as the contact angle measurements indicated a superhydrophobic behaviour for the untreated film and hydrophilic once treated. Based on the XPS analysis, we also found that the hydrophilicity behaviour is probably due to the formation of the S-N polar group on the surface of the Sb2S3 films. Intending to further improve the photoelectroactivity of the Sb2S3 films, we studied the effect of the presence of MoSx on the plasma-treated Sb2S3 films. The jphoto for the Sb2S3/MoSx film was −0.89 ± 0.16 mA cm−2 at −0.20 V and that corresponded to a 2.2-fold increase. The jphoto gain is due to the reduction of the Rct as observed from the impedance experiments. The presence of the MoSx also resulted in a shift of ca. 100 and 280 mV towards less negative values of the Eonset and the Efb, respectively. This suggested that the MoSx behaved as a cocatalyst for the HER. At last, we achieved an even more substantial jphoto of −2.15 mA cm−2 at −0.20 V for the Sb2S3/MoSx film having a delimited geometrical area by placing a teflon mask.